PENGARUH PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN DAN STRUKTUR ASET TERHADAP STURKTUR MODAL (Studi Empiris Perusahaan Retail Trade yang Terdaftar di BEI Periode 2019-2021) - LAILA, SUSMA; YUSRIWARTI, YUSRIWARTI (Fakultas Ekonomi Universitas Islam Indragiri, 2024)
This study aims to determine and obtain empirical evidence of the effect of sales growth, company size and asset structure on the capital structure of Retail Trade companies listed on the IDX. The sample selection process uses purposive sampling. The samples in this study are Retail Trade companies listed on the IDX for the 2019-2021 period as many as 19 companies with a total observation period of 3 years so that the total number is 57 samples. The type of data used in this study is secondary data obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The analysis technique uses statistical calculations through SPSS version 26, while the methods used in this study are Descriptive Statistical Test, Classical Assumption Test, and Hypothesis Test using Multiple Linear Regression Test, T Test, F Test, and Determination Coefficient Test. The results of this study show that Sales Growth affects the Capital Structure of Retail Trade listed on the IDX in 2019-2021. The size of the Company affects the Capital Structure of Retail Trade listed on the IDX in 2019-2021. The Asset Structure does not affect the Retail Trade Capital Structure listed on the IDX in 2019-2021. And Sales Growth, Company Size, Asset Structure simultaneously affect the Capital Structure of Retail Trade Companies listed on the IDX in 2019-2021.